Efficacy for Lidocaine and Articaine in Inferior Alveolar Nerve Block - A Comparative Study - Rakhi S. Purkayastha; Samir Joshi; Krishnanunni Nair; Sudhir Pawar (Wolters Kluwer Medknow Publications, 2024)
Aims: Compare the efficacy of 2% lidocaine with adrenaline (1:200,000) and 4% articaine with adrenaline (1:100,000) in inferior alveolar nerve block prior to extraction of bilateral teeth posterior to canine in interval of one week. Methods and Material: Thirty-five patients were selected for the study. Patients were divided into two different groups: Group 1 - (2% lignocaine with adrenaline (1:200,000)) and Group 2 - (4% articaine with adrenaline (1:100,000)) solution. The study variables for each anaesthetic agent were: onset of action and depth of anaesthesia. A pulp tester was used to demonstrate quantitative values and a visual analogue scale (VAS) was used for qualitative evaluation of the two anaesthetic drugs in 2 min cycle for 10 min with respect to test canine. Anaesthesia was considered successful when pulp tester value 64 was achieved in 10 min for both the anaesthetic agent. Statistical Analysis Used: The difference in the efficacy of lignocaine and articaine was analysed using Student's t test. Within group comparison of the response to the pulp vitality test and VAS over various time periods was analysed using repeated measures Analysis of Variance (ANOVA) with post-hoc Bonferroni test. Results: Data analysis showed statistical differences in onset and depth of anaesthesia between the two groups (P < 0.05). Conclusions: 4% Articaine with adrenaline (1:100,000) onset of action is faster and depth of anaesthesia is better compared to 2% lignocaine with adrenaline (1:200,000). Many previous studies reported onset of anaesthesia, but this study evaluates onset and depth of both the anaesthetic agent quantitatively and qualitatively.